(untitled) (World Bulletin of Public Health, 2026)
Periodontal diseases, including gingivitis and periodontitis, represent a significant public health challenge globally, particularly in low- and middleincome regions where access to oral healthcare remains limited. Central Asia, encompassing Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, and Uzbekistan, faces a rising absolute burden due to population growth and aging, though age-standardized rates show relative stability or modest declines. This paper compares key epidemiological indicators—prevalent cases, incidence, prevalence rates, and disability-adjusted life years (DALYs)—for periodontal diseases in these five countries using data from the Global Burden of Disease (GBD) Study 2021. Findings highlight substantial absolute increases in cases from 1990 to 2021 across the region, driven primarily by demographic changes, with age-standardized metrics indicating no major worsening of per-person risk. Uzbekistan exhibits the largest absolute case numbers, while regional patterns align with broader Asian trends where Central Asia shows relatively high age-standardized incidence rates compared to some subregions. These results underscore the need for targeted prevention in Central Asia to mitigate future burdens amid ongoing demographic shifts.